Association between gastrointestinal disorders and migraine: an integrative review - Cristina Kanazawa, Carla; Malgarin, Juliane Soldi; Esmanhotto, Bruno Bertoli (Headache Medicine, 2024)
Introduction Migraine is a highly incapacitating type of primary headache, characterized by high prevalence and symptoms lasting from 4 to 72 hours. It is typically unilateral and pulsatile, often accompanied by nausea, hypersensitivity to sensory stimuli, vomiting and intense fatigue, and it may or may not be preceded by an aura. Although the pathophysiology of migraine is not completely understood, several mechanisms involving the gut-brain axis may explain the association between migraine and gastrointestinal disorders. Objective This review aims to analyze the influence of gastrointestinal disorders on migraine. Methods An integrative review was conducted by surveying articles in the LILACS, PubMed, and Scielo databases using relevant descriptors related to migraine and gastrointestinal disorders. Results The research identified 31 articles, of which only 11 met the previously established criteria. All eligible articles demonstrated a correlation between migraine and gastrointestinal disorders, with Irritable Bowel Syndrome (IBS) being the most frequently mentioned condition. Conclusion Gastrointestinal disorders influence migraine, possibly through tryptophan metabolism and its associated pathways. Understanding these mechanisms may lead to new treatments. IBS stands out among the disorders associated with migraine, suggesting an integrative approach. Changes in diet and lifestyle, along with medications, are recommended. Early identification of comorbidities can facilitate more effective migraine management. However, further research is needed to develop more effective treatments.